2006
DOI: 10.1523/jneurosci.3607-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Basis of the Slow (<1 Hz) Oscillation in Neurons of the Nucleus Reticularis ThalamiIn Vitro

Abstract: During deep sleep and anesthesia, the EEG of humans and animals exhibits a distinctive slow (Ͻ1 Hz) rhythm. In inhibitory neurons of the nucleus reticularis thalami (NRT), this rhythm is reflected as a slow (Ͻ1 Hz) oscillation of the membrane potential comprising stereotypical, recurring "up" and "down" states. Here we show that reducing the leak current through the activation of group I metabotropic glutamate receptors (mGluRs) with either trans-ACPD [(ϩ/Ϫ)-1-aminocyclopentane-trans-1,3-dicarboxylic acid] (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 53 publications
(102 reference statements)
9
161
1
Order By: Relevance
“…Moreover, thalamic cells present intrinsic properties that give them the capability to generate a slow rhythm (26,27). The absence of any thalamic response associated with slow waves or delta waves may appear to be at odds with these neurophysiological data.…”
Section: Comparison With Earlier Positron Emission Tomography and Fmrmentioning
confidence: 99%
“…Moreover, thalamic cells present intrinsic properties that give them the capability to generate a slow rhythm (26,27). The absence of any thalamic response associated with slow waves or delta waves may appear to be at odds with these neurophysiological data.…”
Section: Comparison With Earlier Positron Emission Tomography and Fmrmentioning
confidence: 99%
“…In the thalamus, the mechanism underlying the generation of the "up state" in the slow oscillation critically relies on the window component of the low-voltage-activated Ca 2ϩ current (T type) (Crunelli et al, 2005, Blethyn et al, 2006. Moreover, Ca 2ϩ entry through T-type channels may activate I CAN (Bal and McCormick, 1993).…”
Section: Ionic Mechanisms Of Prolonged Intrinsic Bursting Activity Inmentioning
confidence: 99%
“…Our experiment specifically focused on the morphological relations between the thalamus and multiple ipsilateral association cortical regions. We chose the thalamus because it acts as the gate of nearly all incoming information to the cortex and plays an important role during natural sleep (Blethyn et al, 2006). In addition, a previous study has shown that SD has a significant effect on the thalamus.…”
Section: Introductionmentioning
confidence: 99%